Real-world study of first-line immunotherapy combined with chemoradiotherapy in esophageal squamous cell carcinoma - Xiaohan Zhao; Chengang Weng; Wuhan Yang; Hongmei Gao; Hesong Wang; Wenzhao Deng; Shuchai Zhu; Wenbin Shen (Scientific Reports)
Abstract This study aimed to assess the effectiveness, safety, and recurrence patterns of first-line immunotherapy combined with chemoradiotherapy in esophageal squamous cell carcinoma (ESCC) patients. A retrospective analysis of 79 eligible ESCC patients was conducted. Primary outcomes included overall survival (OS) and progression-free survival (PFS), with secondary outcomes being objective response rate (ORR), disease control rate (DOR), treatment-related adverse events (trAEs), and treatment failure patterns. The median follow-up was 29.4 months, with median OS unreached and median PFS of 14.6 months (95% CI 10.7–18.5). ORR was 82.3%, and DOR was 96.2%. Factors affecting OS were clinical stage, immunotherapy cycles, immunotherapy and chemoradiotherapy sequence, radiation coverage, mid-treatment lymphocyte count, and short-term efficacy (HR = 2.254, 0.374, 2.653, 2.957, 2.309, 2.789; P = 0.030, 0.019, 0.009, 0.004, 0.001, 0.014). Factors impacting PFS were clinical stage, immunotherapy and chemoradiotherapy, and post-treatment lymphocyte count (HR = 2.135, 2.048, 1.911; P = 0.007, 0.010, 0.001). Among the cohort, 46.8% experienced treatment failure, with 33 receiving second-line treatment, resulting in a median OS of 14.17 months (95% CI 7.303–21.037) and 1- and 2-year OS rates of 56.7% and 24.3%. Notably, 36.7% experienced grade ≥ 2 trAEs, bone marrow suppression most commonly happened, and 5.1% developed esophageal fistulas. Immunotherapy combined with chemoradiotherapy demonstrates strong anti-tumor activity and tolerability in ESCC patients, The radiation for all leisions, sequential immunotherapy combined with chemoradiotherapy, and higher levels of lymph node cell counts are associated with a better prognosis. Large-scale randomized controlled trials are needed for further validation.